White Matter Necrosis in Neonates - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The neuropathologic and ultrasonographic findings in 22 very low birth weight infants surviving at least 6 days are described from Michigan State University, East Lansing, MI., St. Luke's Roosevelt Medical Center and New York Hospital Cornell Medical Center, NY.